2016
DOI: 10.3390/nu9010010
|View full text |Cite
|
Sign up to set email alerts
|

Methionine and Choline Supply during the Periparturient Period Alter Plasma Amino Acid and One-Carbon Metabolism Profiles to Various Extents: Potential Role in Hepatic Metabolism and Antioxidant Status

Abstract: The objective of this study was to profile plasma amino acids (AA) and derivatives of their metabolism during the periparturient period in response to supplemental rumen-protected methionine (MET) or rumen-protected choline (CHOL). Forty cows were fed from −21 through 30 days around parturition in a 2 × 2 factorial design a diet containing MET or CHOL. MET supply led to greater circulating methionine and proportion of methionine in the essential AA pool, total AA, and total sulfur-containing compounds. Lysine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 53 publications
2
39
1
Order By: Relevance
“…Because a previous study detected greater plasma concentrations of several essential and nonessential AA around parturition in response to feeding RPM (Zhou et al, 2016b), we speculate that the upregulation (mRNA and protein) of AA transporters in adipose tissue would be reflective of a greater degree of uptake from plasma. Clearly, systemic concentrations of AA around parturition would be driven in part by DMI and utilization by the mammary gland at the onset of lactation.…”
Section: Discussionmentioning
confidence: 82%
“…Because a previous study detected greater plasma concentrations of several essential and nonessential AA around parturition in response to feeding RPM (Zhou et al, 2016b), we speculate that the upregulation (mRNA and protein) of AA transporters in adipose tissue would be reflective of a greater degree of uptake from plasma. Clearly, systemic concentrations of AA around parturition would be driven in part by DMI and utilization by the mammary gland at the onset of lactation.…”
Section: Discussionmentioning
confidence: 82%
“…Several benefits of feeding rumen-protected Met on improvements of production and health have been reported recently (Osorio et al, 2014;Zhou et al, 2016b;Batistel et al, 2018), with the Met cycle playing an important role from a physiologic standpoint. In the present study, the undetectable expression of PEMT, which catalyzes the formation of phosphatidylcholine upon binding the methyl group from S-adenosylmethionine to phosphatidylethanolamine, likely explains the inability of PMNL to use methyl groups to synthetize phosphatidylcholine, an important molecule in Figure 4.…”
Section: Methionine Cyclementioning
confidence: 99%
“…We observed moderate increases in serum Met (17 and 35% on d 10 and 12, respectively) with a reduction in the Lys-to-Met ratio. In comparison, Zhou et al (2016a) reported a 55% increase in plasma Met levels during the peripartal period in response to RP Met supplementation (6.9 vs. 9.2 g/d of Met, prepartum vs. postpartum, respectively). As for NEAA, MDS tended to increase circulating Cys concentrations.…”
Section: Discussionmentioning
confidence: 87%